2006
DOI: 10.1016/j.neuron.2006.10.008
|View full text |Cite
|
Sign up to set email alerts
|

The Familial Parkinsonism Gene LRRK2 Regulates Neurite Process Morphology

Abstract: Mutations in LRRK2 underlie an autosomal-dominant, inherited form of Parkinson's disease (PD) that mimics the clinical features of the common "sporadic" form of PD. The LRRK2 protein includes putative GTPase, protein kinase, WD40 repeat, and leucine-rich repeat (LRR) domains of unknown function. Here we show that PD-associated LRRK2 mutations display disinhibited kinase activity and induce a progressive reduction in neurite length and branching both in primary neuronal cultures and in the intact rodent CNS. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

48
602
6
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 532 publications
(665 citation statements)
references
References 17 publications
48
602
6
5
Order By: Relevance
“…SakaguchiNakashima et al (2007) showed that mutations in the C. elegans LRK-1 gene, the only LRRK gene present in this species, generate anomalies in the localization of synaptic vesicle proteins. This result, which involves LRRK gene products in the regulation of vesicular transport, agrees with functional data for human LRRK2, which implicates it in synaptic vesicle recycling and neurite outgrowth (MacLeod et al 2006;Hatano et al 2007). Even more striking were the results obtained by Lee et al (2007), showing that loss of function of the LRKK gene of D. melanogaster leads to the death of dopaminergic neurons in the fly brain and anomalies in locomotor activity.…”
Section: Discussionsupporting
confidence: 87%
“…SakaguchiNakashima et al (2007) showed that mutations in the C. elegans LRK-1 gene, the only LRRK gene present in this species, generate anomalies in the localization of synaptic vesicle proteins. This result, which involves LRRK gene products in the regulation of vesicular transport, agrees with functional data for human LRRK2, which implicates it in synaptic vesicle recycling and neurite outgrowth (MacLeod et al 2006;Hatano et al 2007). Even more striking were the results obtained by Lee et al (2007), showing that loss of function of the LRKK gene of D. melanogaster leads to the death of dopaminergic neurons in the fly brain and anomalies in locomotor activity.…”
Section: Discussionsupporting
confidence: 87%
“…When expressed in neuroblastoma cell line or cultured cortical neurons, mutant (G2019S) LRRK2 has been shown to induce apoptotic cell death by activating caspase-3 and caspase-8. [37][38][39] Our results provide the first in-vivo evidence that mutant (G2019S) LRRK2 causes the cell death of SN dopaminergic neurons by activating caspase-9 and caspase-8 through MKK4-JNK-c-Jun pathway.…”
Section: Discussionmentioning
confidence: 62%
“…LRRK2 was found to be associated with membranous structures and vesicles in the mammalian brain 120 and enriched in the Golgi complex 42, 94 at the extent that mice with wild‐type and G2019S ‐LRRK2 overexpression presented fragmentation of the Golgi complex 121.…”
Section: Lrrk2 Function In Vesicle Dynamics and Retromer Functionmentioning
confidence: 99%